Kelemahan Konvensi Jenewa 1949 Dalam Menghadapi Dinamika Konflik Bersenjata Modern - Muhammad Adrian fitra yamazaki; Aldo Kurniawan; Febrio Diosi Pratama (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
This study analyzes the weaknesses of the 1949 Geneva Conventions in addressing the dynamics of modern armed conflicts and examines their relevance and effectiveness in providing legal protection for victims of armed conflicts. This research employs a normative legal method with statutory, conceptual, and case approaches. The findings indicate that the 1949 Geneva Conventions contain several limitations, particularly regarding the state-centric nature of legal subjects, the inability to fully accommodate modern military technological developments, and the limited enforcement mechanisms that lack coercive power. Nevertheless, the 1949 Geneva Conventions remain highly relevant within the international humanitarian law system, as reflected in the applicability of fundamental principles, the strengthening effect of the 1977 Additional Protocols, and their recognition in international practice as the primary instrument for the protection of victims of armed conflicts. However, the effectiveness of their implementation still reveals a gap between law in the books and law in action, influenced by the changing nature of armed conflicts and the limitations of international enforcement mechanisms.